Satire and Humour in Jane Austen’s ‘Northanger Abbey’ - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2021)
Northanger Abbey’ is a commentary on as well as satire of the popular Gothic novels of Austen’s era. She was exploiting public interest in the creaky house, creaky older man and frightened virginal young heroine tropes of the era’s popular Gothic novel. As it is in one of the hardest novels of Austen, people miss its satire. Here, we get a brilliant satire on the ridiculousness of the events, settings, and emotions of gothic novels in general. How to cite this article:  Priydarshi AK. Satire and Humour in Jane Austen’s 'Northanger Abbey’. J Adv Res Eng & Edu 2019; 4(4): 9-11. DOI: https://doi.org/10.24321/2456.4370.201909